Data Governance Facilitate Digital Transformation of Oil and Gas Industry - Su, Jian; Yao, Shanglin; Liu, He (Frontiers in Earth Science, 2022)
Data gradually becomes a critical concern for the strategic resources in enterprises. Massive amounts of data with different types involved in the oil and gas industry can be obtained through IoT (Internet of Things) devices, supported by Blockchain technology with characteristics of immutability and credibility in distributed storage. Hence, credible data will be rationally used in Big Data analysis and Artificial Intelligence implementation. The global mutual trust protocol of Blockchain technology is the bridge among IoT devices, Big Data analysis and Artificial Intelligence implementation, and enables effective coordination of participation of multiple parties and ultimately break isolated island of information. Data governance is the prerequisite for data sharing. As a basic project, Data Sharing breaks data islands and business barriers, improving Data Governance capabilities in Digital Transformation and promoting high-quality development of the oil and gas industry) From the perspective of Digital Transformation, this paper reviews the current situation and problems of Data Governance by evaluating the Data Governance ability of oil and gas enterprises. Furthermore, a proposal is put forward to apply Blockchain technology to improve the Data Governance system and capabilities as the overall program of the oil and gas industry Data Governance system.